PENINGKATAN PARTISIPASI SISWA DENGAN MODEL INKUIRI BERBASIS CTL (CONTEXTUAL TEACHING AND LEARNING) PADA PEMBELAJARAN KEWARGANEGARAAN - Muh Sukemi, Buchory; Sukemi, Samid, Sukemi, Samid; Rusdijati, Rusdijati (Jurnal Cakrawala Pendidikan, 2016)
This article is about a classroom action research concerned with the research problem of whether learners’ participation in Class XI IPA 2 at State Senior High School 1, Jetis, Bantul, Yogyakarta, in the civics education class could be improved with the inquiry learning model based on the concept of Contextual Teaching and Learning (CTL). The research was intended to improve the learners’ participation and to describe their learning achievement in the civics education class employing the inquiry learning model based on CTL. The classroom action research was carried out through a procedure consisting of the following steps: (l) action planning to prepare for the research and for conventional learning performance; (2) action implementation in two cycles; (3) observation, in which any phenomenon taking place during the implementation of the study was observed and recorded; and (4) action evaluation and reflection, in which the weaknesses, insufficiencies, difficulties, and efficacies in improving students’ participation were identified. The subjects of this research were students of Class XI IPA 2 at State Senior High School 1, Jetis, Bantul, Yogyakarta. The research results revealed the following findings: (1) with the inquiry learning model based on CTL, students’ participation in the civics education class could be improved from the active participation of 15 students (39%) in cycle 1 to that of 33 students (87 %) in cycle 2 and (2) students’ learning achievement in the civics education class could be improved from the positive achievement of 17 students (45 %) in cycle 1 to that of 37 students (97 0/0) in cycle 2